2023
DOI: 10.3390/curroncol30030210
|View full text |Cite
|
Sign up to set email alerts
|

Patient Engagement in Health Research: Perspectives from Patient Participants

Abstract: Background and purpose: Over the past decade, patient engagement (PE) has emerged as an important way to help improve the relevance, quality, and impact of health research. However, there is limited consensus on how best to meaningfully engage patients in the research process. The goal of this article is to share our experiences and insights as members of a Patient Advisory Committee (PAC) on a large, multidisciplinary cancer research study that has spanned six years. We hope by sharing our reflections of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Our success in maintaining virtual engagement over time may be in part due to our use of two helpful frameworks: Carman et al’s Multidimensional Framework for Patient and Family Engagement in Health and Health Care and VAV [ 20 , 21 ]. Both frameworks were developed in partnership with patients and strive to support researchers in partnering with patients in a thoughtful, intentional way, which previous research has shown is critically important [ 19 , 29 ]. While neither was developed specifically for virtual engagement, we found both frameworks to be valuable in planning our engagement approach.…”
Section: Discussionmentioning
confidence: 99%
“…Our success in maintaining virtual engagement over time may be in part due to our use of two helpful frameworks: Carman et al’s Multidimensional Framework for Patient and Family Engagement in Health and Health Care and VAV [ 20 , 21 ]. Both frameworks were developed in partnership with patients and strive to support researchers in partnering with patients in a thoughtful, intentional way, which previous research has shown is critically important [ 19 , 29 ]. While neither was developed specifically for virtual engagement, we found both frameworks to be valuable in planning our engagement approach.…”
Section: Discussionmentioning
confidence: 99%
“…Responsiveness of the research team (and how parents valued this) was a major theme within the qualitative data. The importance of assessing the effectiveness of patient engagement approaches and being responsive to feedback through adjustments and improvement has been previously highlighted in the literature as critical to achieve engagement [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future qualitative research on real experiences should also be encouraged to document the local challenges of PPI in scaling as experienced on the ground. 78 …”
Section: Discussionmentioning
confidence: 99%